Atopic eczema and obesity: a population‐based study*. (1st May 2021) - Ascott, A.; Mansfield, K.E.; Schonmann, Y.; Mulick, A.; Abuabara, K.; Roberts, A.; Smeeth, L.; Langan, S.M.
Summary: Background: Atopic eczema is a common chronic inflammatory skin disease. Research suggests an association between atopic eczema and obesity, with inconsistent evidence from European populations. Objectives: To explore the association between diagnosed atopic eczema and being overweight or obese, and whether increased atopic eczema severity was associated with higher body mass index. Methods: We undertook a cross‐sectional analysis within a cohort of adults (matched by age, sex and general practice) with and without a diagnosis of atopic eczema. We used primary care (Clinical Practice Research Datalink Gold) and linked hospital admissions data (1998–2016). We used conditional logistic regression to compare the odds of being overweight or obese (adjusting for confounders and potential mediators) in those with atopic eczema (mild, moderate and severe, and all eczema) vs. those without. Results: We identified 441 746 people with atopic eczema, matched to 1 849 722 without. People with atopic eczema had slightly higher odds of being overweight or obese vs. those without [odds ratio (OR) 1·08, 95% confidence interval (CI) 1·07–1·09] after adjusting for age, asthma and socioeconomic deprivation. Adjusting for potential mediators (high‐dose glucocorticoids, harmful alcohol use, anxiety, depression, smoking) had a minimal impact on effect estimates (OR 1·07, 95% CI 1·06–1·08). We saw no evidence that odds of being overweight or obese increased with increasing atopic eczema severity, and there was no association in people with severe eczema. Conclusions: We found evidence of a small overall association between atopic eczema and being overweight or obese. However, there was no association with obesity among those with the most severe eczema. Our findings are largely reassuring for this prevalent patient group who may already have an increased risk of cardiovascular disease.